2022
DOI: 10.1108/ijge-06-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

Refugee women's entrepreneurship: where from and where to next?

Abstract: PurposeThis reflective paper offers an overview on how refugee women's entrepreneurship scholarship evolved, and suggests research directions for the future development of the field.Design/methodology/approachA reflective approach encompassing the evolvement of the field of refugee women's entrepreneurship research.FindingsWhilst refugee women's entrepreneurship scholarship and research, and its interlinks with resilience, empowerment, gender, and livelihoods theoretical framings have flourished in recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This research emphasizes the need to diversify support frameworks for refugee entrepreneurs beyond typical models and guidelines to meet their unique needs (Akbar & Siti-Nabiha, 2022;Hassan et al, 2021). It has been discovered that successful immigrant entrepreneurs have a command of the language of the country in which they are settling, an education or training, previous experience in business, support from family and social networks, and access to suppliers and customers located within their communities (Al-Dajani, 2022;Schmich & Mitra, 2023). Additionally, it is observed that there is a difference between refugee entrepreneurs operating in metropolitan settings and those operating in camps.…”
Section: Enabling Refugee Entrepreneurship Through Islamic Microfinancementioning
confidence: 99%
See 1 more Smart Citation
“…This research emphasizes the need to diversify support frameworks for refugee entrepreneurs beyond typical models and guidelines to meet their unique needs (Akbar & Siti-Nabiha, 2022;Hassan et al, 2021). It has been discovered that successful immigrant entrepreneurs have a command of the language of the country in which they are settling, an education or training, previous experience in business, support from family and social networks, and access to suppliers and customers located within their communities (Al-Dajani, 2022;Schmich & Mitra, 2023). Additionally, it is observed that there is a difference between refugee entrepreneurs operating in metropolitan settings and those operating in camps.…”
Section: Enabling Refugee Entrepreneurship Through Islamic Microfinancementioning
confidence: 99%
“…This study is important because it examines how Islamic microfinance can empower Rohingya refugees in Bangladesh (Abdul Zalim, 2022;Al-Dajani, 2022;Purwanto et al, 2022). The results will benefit policymakers, practitioners, and humanitarian organizations in refugee environments.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in emerging economies the potential emancipatory and empowering influence of women’s agency remains more muted. The notion of “restricted agency” (Al-Dajani, 2022; Anderson and Ojediran, 2022) has been proposed to describe the constraints faced by women entrepreneurs in specific contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship research and family entrepreneurship literature is still dominated by publications that address the developed contexts in the Global North (Contreras and Dornberger, 2022). However, entrepreneurship has an increasing importance in development agendas in the Global South, in particular as an emancipatory tool for women’s social and economic advancement and women’s empowerment (Al-Dajani, 2022; Ojediran and Anderson, 2020; Bastian et al , 2019). Thus, the inclusion of this regional perspective enriches the existing literature, providing a more globally representative understanding of the interplay between family entrepreneurship, gender equality and women's empowerment.…”
Section: Introductionmentioning
confidence: 99%